Disproportionation of O -Methylhydroxylamine Catalyzed by Aquapentacyanoferrate(II) - Gutiérrez, María M. (2011)
The aquapentacyanoferrate(II) ion, [FeII(CN)5H2O]3-, catalyzes the disproportionation reaction of O-methylhydroxylamine, NH2OCH3, with stoichiometry 3 NH2OCH3 ==0 NH3 + N2 + 3 CH3OH. Kinetic and spectroscopic evidence support an initial N coordination of NH2OCH3 to [FeII(CN)5H2O]3- followed by a homolytic scission leading to radicals [FeII(CN)5•NH2]3- (a precursor of Fe(III) centers and bound NH3) and free methoxyl, CH3O•, thus establishing a radical path leading to N-methoxyamino (•NHOCH3) and 1,2-dimethoxyhydrazine, (NHOCH3)2. The latter species is moderately stable and proposed to be the precursor of N2 and most of the generated CH3OH. Intermediate [FeIII(CN)5L]2- complexes (L = NH3, H2O) form dinuclear cyano-bridged mixed-valent species, affording a catalytic substitution of the L ligands promoted by [FeII(CN)5L]3-. Free or bound NH2OCH3 may act as reductants of [FeIII(CN)5L]2-, thus regenerating active sites. At increasing concentrations of NH2OCH3 a coordinated diazene species emerges, [FeII(CN)5N2H2]3-, which is consumed by the oxidizing CH3O•, giving N2 and CH3OH. Another side reaction forms [FeII(CN)5N(O)CH3]3-, an intermediate containing the nitrosomethane ligand, which is further oxidized to the nitroprusside ion, [FeII(CN)5NO]2-. The latter is a final oxidation product with a significant conversion of the initial [FeII(CN)5H2O]3- complex. The side reaction partially blocks the Fe(II)aqua active site, though complete inhibition is not achieved because the radical path evolves faster than the formation rates of the FeIINO+ bonds.